Knock-Down of Mucolipin 1 Channel Promotes Tumor Progression and Invasion in Human Glioblastoma Cell Lines - Santoni, Giorgio; Amantini, Consuelo; Nabissi, Massimo; Maggi, Federica; Arcella, Antonietta; Marinelli, Oliviero; Eleuteri, Anna Maria; Santoni, Matteo; Morelli, Maria Beatrice (Frontiers in Oncology, 2021)
Among cancers that affect the central nervous system, glioblastoma is the most common. Given the negative prognostic significance of transient receptor potential mucolipin 1 (TRPML1) channel reduction in glioblastoma patients previously published, the aim of the current study was to investigate the biological advantage of TRPML1 loss for glioma cells. Human glioblastoma primary cancer cells (FSL, FCL) and glioblastoma cell lines (T98, U251) were used to that purpose. TRPML1 silencing in T98 cells induces defective autophagy, NO production and cathepsin B-dependent apoptosis in the first 48 h and then apoptotic resistant cells proliferate with high growth rate respect to control cells. In U251 cells, knock-down of TRPML1 stimulates NO generation and protein oxidation, arrests cell cycle at G2/M phase and induces autophagy leading to cathepsin B-dependent senescence. Finally, in both cell lines long-term effects of TRPML1 silencing promotes survival and invasion capacity respect to control cells. Silencing of TRPML1 expression affects also glioblastoma primary cells’ phenotype. FSL cells show increased proliferation ability, while FCL cells enter into senescence associated with an increased invasion ability. In conclusion, although the molecular heterogeneity among different glioblastoma cancer cells, our data support TRPML1 down-regulation as negative prognostic factor in glioblastoma.